MODEL PENGEMBANGAN AGROINDUSTRI PERIKANAN BERBASIS PARTISIPASI MASYARAKAT : STUDI KASUS DAERAH CILACAP-JAWA TENGAH - Y.A. Budhi Jatmiko; John Haluan; Mita Wahyuni; Hartrisari Hardjomidjojo (Buletin PSP, 2007)
Model of the development of Fishery agro industry base on the society participation addressed to increase regional economics. Criteria of development agro industry besides relied on criteria of legibility financial, but is also relied on a real circumstance is the area. Model develop builded consisted of three sub model that is pre-eminent commodity election, pre-eminent product election and election analyze the financial. Pre-Eminent commodity selected by pursuant to economic value and sum up the commodity which not yet been permeated by industry. Superlative product determined by pursuant to real circumstance is area so that only need a few/little socialization touch and innovate especially from technological facet. criteria of Legibility financial used by Net Present Value ( NPV), Pay Back Period ( PBP) And Benefit Cost Ratio ( B / C Ratio). For the area of Cilacap, alternative of development of agro industry fishery base on the society involvement fish jelly product. Strategy of operational of development of agro industry fishery base on the society participation divided into three phases, that are early stage development, phase of growth and phase of maturation agro industry.